Species diversity and geographical distribution of ticks infesting domestic animals in Bagmati Province, Nepal - Kamana Thapa; Chet Raj Pathak; Somnath Aryal; Surendra Prasad Kanu (PLoS ONE, 2026)
Background Ticks are important vectors for bacterial, viral, rickettsial, and protozoal diseases in different animals and humans, especially in tropical countries. Tick-borne pathogens (TBPs) are host and vector-species-specific and depict geographical variations. This study was conducted to determine the diversity of ticks and their geographical distribution among domestic animals. Methodology/Principal Findings Ticks were collected from a total of 210 domestic animals: cattle (n = 30), buffaloes (n = 40), sheep (n = 50), goats (n = 30), and dogs (n = 60), representing Chitwan (Terai), Kathmandu (mid-hill), and Rasuwa (high-hill) of Nepal. The genus and species of ticks were identified using morphological keys under a stereomicroscope. Analysis was performed using MS Excel, and Shannon-Wiener’s and Simpson’s diversity indexes were calculated. A total of 4 genera of hard ticks were observed, representing Rhipicephalus , Haemaphysalis , Dermacentor , and Hyalomma . Among them, Rhipicephalus (Boophilus) microplus (30.42%) was most abundant, followed by Haemaphysalis longicornis (26.74%), Rhipicephalus sanguineus (18.8%), Haemaphysalis sulcata (13.23%), and Rhipicephalus decoloratus (2.86%). Similarly, Haemaphysalis spp. (2.18%), Haemaphysalis leachi (2.05%), Dermacentor sp. (1.36%), Rhipicephalus spp. (1.36%), Hyalomma sp. (0.41%), and Rhipicephalus parva (0.14%). Geographical distribution and tick species diversity were higher in Chitwan. Similarly, species diversity in the case of the host was found to be greater in small ruminants. The result suggested higher tick distribution and diversity among warm tropical regions of Nepal. Conclusions This study investigates the distribution of ticks ( Haemaphysalis , Rhipicephalus , Dermacentor , and Hyalomma ) in domestic animals across various climatic conditions, identifying the high-risk areas and animal species for tick-borne diseases, including zoonoses. The findings highlight the need for advanced research on tick ecology, epidemiology of TBPs, and the implementation of effective control strategies.